Luxury fashion purchase intention differences across cultural dimensions - Kansa, Aino (My University, 2025)
Luxuries have been present since the antiquity and since then certain consumers have been willing to pay a premium price on items that may not be viewed as necessities for survival. As globalization and digitalization have expanded the accessibility of luxury brands, consumers now engage with luxury fashion for increasingly diverse reasons that go beyond simple notions of wealth and exclusivity. Understanding the psychological and cultural factors that drive luxury purchase intentions is therefore essential for explaining how and why individuals want to purchase expensive luxury fashion items. The aim of this thesis is to investigate luxury purchase intention and the differences found across cultural dimensions. To help approach the aim, two subquestions were formed: What makes a consumer buy luxury fashion? and How does culture influence luxury fashion purchase intention? To address these subquestions, the thesis first examines general consumer behaviour model by Kotler and Armstrong (2017), followed by luxury-specific models by Vigneron and Johnson (2004) and Wiedmann et al. (2007). These models together with supporting articles were used in order to create an understanding on the determinants of luxury fashion purchase intention. The second subquestion was investigated through Hofstede’s cultural dimensions model, which enabled the categorization of cultural differences in luxury purchase intention across cultures found in the literature. The findings indicate that luxury fashion purchase intention is driven by three categories of determinants: (1) financial and functional values, (2) the expressive role of luxury, i.e. personality antecedents and (3) the instrumental role of luxury, i.e. the socio-psychological antecedents. Cultural comparisons did not reveal many generalisable differences between high and low scores on the cultural dimensions. The most influential cultural dimension seems to be power distance, which influenced the status consumption and normative influence. Other findings from literature were mixed or suggested the antecedents of luxury fashion purchase intention to be universal and thus be important across cultures. Overall, the findings in this thesis highlight that luxury fashion purchase intention formation is multidimensional and complex construct and that there are potential variations in the motivations and values linked to luxury fashion purchase intention across cultures. The findings can be beneficial for luxury brands when deciding on whether to standardise or localise marketing materials in culturally different nations.

Luksustuotteita on kulutettu jo antiikin ajoista lähtien, ja siitä lähtien tietyt kuluttajat ovat olleet valmiita maksamaan korkeampaa hintaa tuotteista, joita ei voida pitää eloonjäämisen kannalta välttämättöminä. Globalisaation ja digitalisaation myötä luksusbrändien saatavuus on kasvanut ja kuluttajat hankkivat luksustuotteita yhä monipuolisemmista syistä, jotka ylittävät perinteiset käsitykset varakkuudesta tai eksklusiivisuudesta. Psykologisten ja kulttuuristen taustatekijöiden ymmärtäminen on olennaista, jotta voidaan ymmärtää, miten ja miksi yksilöt haluavat ostaa kalliita luksusmuotituotteita. Tämän kandidaatintutkielman tarkoituksena on tarkastella luksusmuodin ostoaietta ja kulttuuristen ulottuvuuksien välisiä eroja. Tämän saavuttamiseksi muodostettiin kaksi osaongelmaa: Mikä saa kuluttajan haluamaan ostaa luksusmuotia? sekä Miten kulttuuri vaikuttaa luksusmuodin ostoaikeisiin? Ensimmäistä osaongelmaa lähestyttiin Kotlerin ja Armstrongin (2017) yleisen kuluttajakäyttäytymisen mallin avulla, jonka jälkeen tarkasteltiin kahta luksuskulutukseen keskittynyttä mallia (Vigneron & Johnson 2004; Wiedmann et al. 2007). Näitä malleja sekä kirjallisuutta hyödyntämällä muodostettiin kokonaiskuva luksusmuodin ostoaikeen taustatekijöistä. Toista osaongelmaa tarkasteltiin Hofsteden kulttuurin dimensioiden mallin avulla, mikä mahdollisti kirjallisuudessa esiin tulleiden luksusmuodin ostoaikeeseen liittyvien kulttuuristen erojen kategorisoinnin ja vertailun. Löydökset osoittavat, että luksusmuodin ostoaietta ohjaavat tekijät voidaan jakaa kolmeen ryhmään: (1) taloudelliset ja funktionaaliset arvot, (2) luksuksen ilmaisuvoimainen rooli eli persoonallisuuteen liittyvät tekijät sekä (3) luksuksen välineellinen rooli eli sosiaalipsykologiset tekijät. Kulttuurien väliset vertailut eivät paljastaneet monia yleistettävissä olevia eroja kulttuuristen ulottuvuuksien korkeiden ja matalien pistemäärien välillä. Vaikuttavimmaksi kulttuuriseksi ulottuvuudeksi osoittautui valtaetäisyys, joka vaikutti erityisesti statukseen perustuvaan kuluttamiseen sekä normatiiviseen vaikutukseen. Muut kirjallisuudesta löytyneet havainnot olivat pitkälti ristiriitaisia tai viittasivat siihen, että luksusmuodin ostoaikeen taustatekijät ovat suurelta osin universaaleja ja siten merkityksellisiä eri kulttuureissa. Yhteenvetona löydökset korostavat, että luksusmuodin ostoaikeen muodostuminen on moniulotteinen ja monimutkainen ilmiö. Eri kulttuureissa saattaa kuitenkin esiintyä vaihtelua motivaatiotekijöissä sekä arvoissa, jotka ohjaavat luksusmuodin ostoaietta. Löydökset voivat tarjota hyödyllistä tietoa luksusbrändeille, kun he tekevät päätöksiä, tulisiko markkinointiviestintää yhtenäistää vai mukauttaa eri kulttuurien mukaisesti.
Keywords: luxury fashion, consumer behaviour, purchase intention, cultural dimensions, psychological drivers, status consumption